iLukBa ver 1.1 : indoor user location system with speech recognition for mobile users - Mantoro, Teddy; Borovac, Amir (2010)
location for mobile user. It works with small mobile devices such as PDAs and it is combined with the speech recognition systems on how the environment response delivered to the location of the user. It has been developed using an advanced and robust algorithm in determining user location for indoor environment which offers location precision accuracy in small room scale. iLukBa capable to handle the unpredictability of IEEE 802.11 (Wifi) signals across perturbation in space, and in time (diurnally) by using Wifi's signal strenght.iLukBa also provides direct service delivery when a user on the move from on location to another, the environment response in delevering service is based on the speed of user.Dynamic buffer is created, the buffer size depends on the speed of the user. The faster a user moves, the smaller the buffer in delevering the speech.iLukBa is a proof of concept of a low cost smart environment capability , i.e. indoor user location can be determined and the environment response can be delivered using speech recognition based on indoor user location.